ACTIVE CHARCOAL FROM WASTE OF AVOCADO SEEDS AS A CHROMIC (CR) METAL ADSORBENT USING CHLORIDE ACID (HCL) AND SULFURIC ACID (H2SO4) ACTIVATOR - Dody Guntama; Ika Mahardini; Regzinta Purnamasari; Lukman Nulhakim (Journal of Community Based Environmental Engineering and Management, 2020)
Avocado seeds are one of the wastes generated from restaurants that serve avocado juice. This avocado seed waste can be used as activated charcoal by carbonization at high temperatures and chemical activation using HCl and H2SO4 activators. The results showed that the optimum concentration of HCl and H2SO4 activator was 5%, which at a concentration of 5% produced the smallest water content values, namely 0.5825% and 0.6763%, the lowest ash content was 0.2993% and 0.2296%, while the adsorption to iodine amounted to 252.2419 mg / g and 279.8959 mg / g. The charcoal from avocado seeds has the potential to absorb chromium metal, which at optimum conditions can absorb 0.1673 mg / L and 0.1535 mg / L.